Pendampingan Penyelesaian Problematika Pembacaan Al-Qur’an Di Tpq Darussalam Dusun Sumber Golek Desa Pranggang Kecamatan Plosoklaten Kabupaten Kediri - Rohmad; Asfiatun Khoti’in (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
The Qur'an is a divine revelation that is a guide and a lesson for those who believe and practice it. Not only that, the Qur'an is also the last holy book revealed by Allah, which includes all the points of Shari'ah contained in the previously revealed holy books. That is why the presence of the Qur'an Education Park in the midst of society has always been a bright spot in solving the basic problem of learning to read the Qur'an. In general, the garden of education of the Qur'an aims in order to prepare its students to become a generation of Qur'an, namely commitment and make the Qur'an as a view of daily life. In particular, the purpose of this program is: (1) able to understand the conditions of the Qur'an that have been determined (2) children can read the Qur'an well (3) children can understand short length, harakat well (4) Love for the Qur'an. By using the method of learning more targeted, with the cohesiveness between teachers and the community, there will be better management of TPQ, researchers and communities and the role of the Pranggang Village community well in succeeding the TPQ teacher development program.